The Impact of Migration on the Welfare of Households in Ghana: A Propensity Score Matching Approach - Abdulai, Abdul-Malik; Boakye-Yiadom, Louis; Quartey, Peter (African Human Mobility Review, 2021)
Individuals usually migrate to improve their economic conditions and those of their family members left behind. However, less is understood about the impact of internal migration on the well-being of family members left behind. This study contributes to the debate by offering an empirical assessment of the welfare difference between migrant and non-migrant households by analysing data recently collected by the Centre for Migration Studies, University of Ghana. Results from the analysis are inconclusive. Using two indicators of measuring welfare (the World Bank Welfare Index and the number of children enrolled in school at the time of the survey), the latter shows higher welfare in favour of non-migrant households whilst the former indicates equality in welfare for all households. On the other hand, econometric estimations using the Propensity Score Matching (PSM) did not find any significant difference between the welfare of households that sent out migrants and those that did not.